Meningkatkan Keputusan Berinvestasi Masyarakat Sidoarjo Melalui Knowledge Management dan pengaruh variabel Financial Literacy, Religiusitas serta Mental Accounting: - - Imelda Dian Rahmawati; Dewi Komalasari; Santi Rahma Dewi; Aulia Putri Saraswati; Fania Nabila Lakadjo (Owner : Riset dan Jurnal Akuntansi, 2023)
This research aims to encourage and foster the younger generation to have financial skills and accounting mentality so they can create a future brighter future. Educate the younger generation about investing by understanding financial literacy, religiosity and mental accounting to avoid online fraud or offline. It's time for millennials to learn skills invest, leave the consumptive lifestyle, and prepare for a better future bright. Knowledge management (knowledge management) is a process that focuses on how knowledge can be managed and used to improve performance. To create a knowledge-based economy then the need for knowledge management in every individual in society. Method research used in this study is a quantitative research method with causality approach, namely looking for evidence of a causal relationship through influence generated between the independent variable and the dependent variable. The data source used is primary data. The population of this study is the millennial generation which is spread throughout the region Sidoarjo. The sampling technique in this study is a convenience technique sampling. Convenience sampling is a method that researchers use to collect market research data from available respondents. Based on the results of the analysis, hypothesis testing and discussion it can be concluded that financial literacy, religiosity and mentality Accounting has a positive and significant effect on generational investment decisions Sidoarjo millennials. Knowledge Management has proven capable of playing a financial mediating role literacy. religiosity, mental accounting for investment decisions in the Sidoarjo community